1990
DOI: 10.1007/bf00142392
|View full text |Cite
|
Sign up to set email alerts
|

Aeolian processes on Venus

Abstract: In this pre-Magellan review of aeolian processes on Venus we show that the average rate of resurfacing is less than 2 to 4 km/Ga, based on the impact crater size frequency distribution derived from Venera observations, reasonable values of the impact flux, and the assumption of steady state conditions between crater production and obliteration. Viscous relaxation of crater topography, burial by volcanic deposits, tectonic disruption, chemical and mechanical weathering and erosion, and accumulation of windblown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 80 publications
0
43
0
Order By: Relevance
“…Only two prominent Greeley and Iversen (1985) and Lodders and Fegley (1998). Tessera (Greeley et al, 1992a(Greeley et al, , 1997. Thousands of wind streaks are seen in the Magellan data, as were some features interpreted to be yardangs, but sand dunes only cover approximately 0.004% of the surface.…”
Section: Dunes On Venusmentioning
confidence: 89%
See 1 more Smart Citation
“…Only two prominent Greeley and Iversen (1985) and Lodders and Fegley (1998). Tessera (Greeley et al, 1992a(Greeley et al, , 1997. Thousands of wind streaks are seen in the Magellan data, as were some features interpreted to be yardangs, but sand dunes only cover approximately 0.004% of the surface.…”
Section: Dunes On Venusmentioning
confidence: 89%
“…The Magellan mission used Synthetic Aperture Radar (SAR) to image more than 98% of the surface of Venus (Saunders et al, 1992), and sand dunes were identified by the specular pattern they produced in some of the SAR images (Greeley et al, 1997). Only two prominent Greeley and Iversen (1985) and Lodders and Fegley (1998).…”
Section: Dunes On Venusmentioning
confidence: 99%
“…Such thin deposits are unlikely to significantly alter either the size or depth of a crater floor, but a number of factors might influence their distribution and development. First, the effect of atmospheric pressure on the saltation threshold [Greeley and Arvidson, 1990] indicates that eolian transport is easiest at low elevations and requires progressively more windspeed at higher elevations. Second, since wind streaks on Venus preferentially occur between -•20 ø and 30 ø north and south latitude , atmospheric circulation may affect the distribution of eolian features on Venus.…”
Section: Eolian Depositsmentioning
confidence: 99%
“…Some martian wind streaks were observed to have changed between Viking observations (Sagan et al, 1973;Thomas and Veverka, 19791, proving that some sort of surface process was presently operating, with the wind being the only reasonable candidate. Most recently, Magellan radar observations of the venusian surface have revealed albedo features that are almost certainly a result of aeolian activity (Saunders et al, 1990;Greeley and Arvidson, 1990;Greeley et al, 1992). The general conditions necessary to generate the albedo contrast that makes the wind streak visible are the focus of this Fig.…”
Section: Introductionmentioning
confidence: 98%